The impact of core training combined with breathing exercises on individuals with chronic non-specific low back pain - Li, Ying; Zhao, Qian; Zhang, Xiao; E, Yan; Su, Yuqin (Frontiers in Public Health, 2025)
BackgroundChronic non-specific low back pain (CNLBP) is a common condition, defined as pain lasting more than 3 months between the lower thoracic margin and gluteal folds, without identifiable tissue damage. Despite its low disability rate, the complex etiology and high recurrence impose significant health and socioeconomic burdens. According to European LBP guidelines, exercise therapy is the preferred treatment for CNLBP. This study evaluates the efficacy of core training combined with breathing exercises as a therapeutic intervention for CNLBP.MethodsEighteen CNLBP patients were randomly assigned to three groups: core training only, core training with breathing exercises, and a control group. A 12-week intervention included VAS, ODI scores, and muscle strength tests.ResultsThe combined group showed significantly greater pain reduction, functional improvement, and muscle strength enhancement compared to the other groups.ConclusionCore training with breathing exercises is more effective in alleviating CNLBP symptoms, highlighting the added value of integrating breathing exercises.